Cardioprotective effects of high‐intensity interval training are mediated through microRNA regulation of mitochondrial and oxidative stress pathways. Issue 6 (10th December 2019) - Jeremic, Nevena; Weber, Gregory J.; Theilen, Nicholas T.; Tyagi, Suresh C.
Abstract: Human studies have shown high‐intensity interval training (HIIT) has beneficial cardiovascular effects and is typically more time‐efficient compared with traditional endurance exercise. The main goal of this study is to show the potential molecular and functional cardiovascular benefits of HIIT compared with endurance training (ET). Three groups of mice were used including sedentary‐control, ET mice, and HIIT mice groups. Results indicated ejection fraction was increased in HIIT compared with ET while fractional shortening was increased in the HIIT group compared with both groups. Blood flow of the abdominal aorta was increased in both exercise groups compared with control. Increases in cross‐sectional area and mitochondrial and antioxidative markers in HIIT compared with control were observed, along with several microRNAs. These findings indicate HIIT has specific cardiac‐protective effects and may be a viable alternative to traditional ET as a cardiovascular preventative medicine intervention. Abstract : Both endurance training (ET) and high‐intensity interval training (HIIT) created beneficial and cardioprotective adaptations, however, there were specific differences between the two exercise groups, including cardiac output, oxidative stress, and microRNA (miRNA) expression. Furthermore, most of the observed molecular and physiological changes in ET were also seen in HIIT groups, indicating HIIT may be a more efficient form of exercise to enhance the contractile, mitochondrial function, antioxidant status, and endocrine response of cardiac muscle tissue. These observed molecular and physiological changes may be regulated by miRNAs, as increased expression of protein markers in the heart were accompanied by decreases in expression of miRNAs predicated to target genes of interest in this study.